Family Business Sustainability through Community Orientation - Filda Rahmiati (International Journal of Family Business Practices, 2020)
This research aims to explore the sustainability of family business through the implementation of Corporate Social Responsibility (CSR) to the community surrounding the company. As many research studies mentioned that family businesses are often strongly anchored in the local community, the high commitment to the local community will leads to a high degree of socially responsible acting. Qualitative method is used in the form of a case of an Indonesian small business in Bogor. The data collection is done using direct methods like observation, interview, and going through the company documentations to comprehend the case situation. The result of the research shows that the CSR implementation, in case observed, was in accordance with the needs of surrounding community. The CSR activities were in the form of the education, religious activities, public facilities, employee and community empowerment. The community and the company were supporting each other in order to make the activity success. This study concludes that this symbiotic CSR could be new model for family business enterprises sustainability through CSR.